2018
DOI: 10.25100/cm.v49i2.3840
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating nutrition as a risk factor for cardio-metabolic diseases

Abstract: Introduction: The consumption of saturated fats is considered a risk factor for cardiovascular diseases.Objective: Review published papers on the role of macro-nutrient intake in cardiovascular risk.Results: Recent reports from the PURE study and several previous meta-analyses, show that the consumption of total saturated and unsaturated fat is not associated with risk of acute myocardial infarction or mortality due to cardiovascular disease. High carbohydrate intake was associated with the highest risk of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
6
0
3
Order By: Relevance
“…A recent cohort involving 18 countries showed that carbohydrate consumption > 65% of energy was associated with a higher incidence of total mortality and mortality related to non-cardiovascular causes compared to 45–65% energy, however, the quality of carbohydrate intake was not addressed in this study [42]. The quality of carbohydrates is also associated with the development of NCD [43], such as added sugars and fructose, present mainly in industrial foods, and low fiber [44]. Studies have shown that consumption of a whole-grain diet is associated with reduced risk of CVD, cancers and total mortality [45].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort involving 18 countries showed that carbohydrate consumption > 65% of energy was associated with a higher incidence of total mortality and mortality related to non-cardiovascular causes compared to 45–65% energy, however, the quality of carbohydrate intake was not addressed in this study [42]. The quality of carbohydrates is also associated with the development of NCD [43], such as added sugars and fructose, present mainly in industrial foods, and low fiber [44]. Studies have shown that consumption of a whole-grain diet is associated with reduced risk of CVD, cancers and total mortality [45].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, vegetarians had higher LDL levels than nonvegetarians. The common possible factor that could explain the high LDL concentration and higher blood pressure levels in vegetarians would be the intake of refined carbohydrates, since their excessive consumption is associated with greater adverse effects not only on the lipid profile, but also on blood pressure [ 49 ]. On the other hand, although blood pressure levels were higher in vegetarians, it is interesting that they do not have a higher BMI than nonvegetarians, since obesity is the main risk factor related to hypertension [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fruits and vegetables are a rich source of exogenic antioxidants, such as vitamins C and E and minerals (Mg, Zn, Mn and Se) and also of non-essential phytochemicals (polyphenols and carotenoids). Numerous studies have shown that a diet rich in fruits and vegetables is associated with reduced risk of chronic diseases (19,20) . In fact, it has been shown that during oxidative stress, dietary components can modify total antioxidant capacity, an analyte frequently used to assess the antioxidant status of biological samples, improving redox status and consequently delaying or preventing progression and onset of diseases.…”
Section: Reactive Oxygen Species: Antioxidant Defence System and Relamentioning
confidence: 99%